Lessons from the British and French New Towns Paradise Lost?. - Fée, David (Emerald Publishing Limited, 2020)
This book explores the evolution of New Towns in France and the UK in a number of areas (governance, planning and heritage) and assess whether their legacy can inspire current planned settlements.